Firms’ Recovery from COVID-19 in Malaysia : Results from the 4th Round of COVID-19 Business Pulse Survey - Kuriakose, Smita; Tran, Trang Thu; Ting, Kok Onn; Hebous, Sarah Waltraut (Washington, DC: World Bank, 2022)
The Coronavirus disease 2019 (COVID-19) business pulse survey (BPS) is a rapid survey designed to measure the various channels of impact of COVID-19 on firms, firm adjustment strategies, and public policy responses. The World Bank, in collaboration with a private survey company, conducted the 4th round of the Malaysia BPS in February to March 2022, following the 1st round in October 2020, 2nd round in Mid-January to February 2021, and 3rd round in July 2021. Firms were sampled randomly from an online business panel database, which consists of 100,000+ companies in all sectors and sizes, across Peninsular and East Malaysia. A minimum sample size was obtained for sectors that are important to Malaysia’s economy and are sensitive to the COVID-19 crisis (export-oriented activities: electronics, automotive, tourism related activities) while preserving the sectoral shares in the sampling frame. The survey was conducted online and yielded 1,500 responses from respondents in senior management positions at their company (i.e. owners, C-suite or Director level).